1967
DOI: 10.1111/j.1469-8986.1967.tb02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Resistance, Sweat‐gland Counts, Salivary Flow, and Gastric Secretion: Age, Race, and Sex Differences, Andintercorrelations

Abstract: Skin resistance, sweat-gland counts, salivary flow, gastric secretion, and pH were measured in volunteers and patients of both sexes, Negroes and Caucasians. Correlational analysis suggested two negatively related clusters: (A) salivary flow, sweat-gland counts, and gastric secretion ; and (B) age, skin resistance, and pH. Skin resistance was higher in Negroes than Caucasians, and in females than males, increasing irregularly with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Sweat gland counts and SR measures 107 were also recorded in parallel by Juniper and Dykman (1967) from different clinical groups of both genders. They confirmed lower SRLs and lower sweat gland counts in African-Americans as compared to Caucasians for both females and males.…”
Section: Ethnic Differences and Heritabilitymentioning
confidence: 99%
“…Sweat gland counts and SR measures 107 were also recorded in parallel by Juniper and Dykman (1967) from different clinical groups of both genders. They confirmed lower SRLs and lower sweat gland counts in African-Americans as compared to Caucasians for both females and males.…”
Section: Ethnic Differences and Heritabilitymentioning
confidence: 99%
“…The active sweat glands for one region (axilla) have not been investigated, so this value was taken to be 90% of that reported in Table 1. Sources: Clark and Lhamon [60], Ogata [63], Randall [64], Thompson [65], Willis et al [66], Roberts et al [78], Sato and Dobson [85], Inoue et al [86], Kondo et al [87], Peter and Wyndham [88], Buono [89], Gibson and Shelley [90], MacKinnon [91] (with the original calculation error corrected), Collins et al, [92], Hellon and Lind [93], Silver et al [94], Ojikutu [95], Sargent and Weinman [96], Juniper and Dykman [97], Toda [98], Bar-Or et al [99], Knip [100], Knip [101], Schaefer et al [102], Catania et al [103], Behm et al [104], Inoue et al [105], Kondo et al [106], Inoue et al [107], Welch et al [108] and Madeira et al [109]. …”
Section: Reviewmentioning
confidence: 99%
“…Studies with aged squirrel monkeys have shown a decreased febrile response to both intravenous and intraventricular injec tion of endotoxin even though leukocytes from aged monkeys produced LP in vitro [Clark et al, 1980]. In addition to a de creased central nervous system response to LP, an aging peripheral vascular system in some elderly persons may result in decreased ability to vasoconstrict, shiver, and drive the core body temperature higher [Collins et ah, 1977;Juniper and Dykman, 1967], Future studies should address these responses to a pyrogenic stimulus in elderly volunteers. In all likelihood, the diminished response of the elderly to infection is multifactorial and not a result of chronological age alone.…”
Section: Discussionmentioning
confidence: 99%